Pelanggaran Asas Imparsialitas Oleh Hakim Pengadilan Negeri Kupang Dalam Perkara 536/Pid.B/2008/PN.KPG - Fahmi, Muhammad; Effendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The court is the last place for the parties to solve problems that occur, because the court considered a place that has equity in accordance with applicable law, the court is run by a judicial peripheral devices such as the Presiding Judge, Judge, the Registrar, the Public Prosecutor and apparatus other countries designated by the State directly, but nowadays in Indonesia itself has raised a lack of confidence by the public towards the judiciary dikarenkan negative behavior caused by the state apparatus itself, as the judge who is in the region of Kupang in particular, the judge has violated the code judicial ethics, because the judge handling his own case, the judge has to know that it was his brother but does not resign, the consequences arising Kupang because the judge does not resign impact on peoples sense of a lack of judicial institutions in Indonesia.Context of judicial independence in a world of justice does not mean that judges are free to do anything in the process of examination and trial, but the judge also has certain limitations, restrictions stipulated in the code of conduct of judges of the judiciary, judges do not assume that all the king should be considered correct decisions , but the judge has rules and limits of its own in the process of investigation or trial.This type of research can be classified in a normative law research which the author examines the judicial authority law and the judicial code of conduct with the legal principles that apply in Indonesia, this research is also reinforced with the interview data to pekanbaru district court judge in order to strengthen the existing data ,Keywords: Court-Judge-Violation of the Code of Justice